Neurological Involvement Complicating Invasive Pulmonary Aspergillosis - Ibrahima Dokal Diallo; Najlae Lrhorfi; Wend-Yam Mohamed Traoré; Behyamet Onka; Latifa Chat; Nazik Allali (SAGE Publishing, 2022)
Cerebral aspergillosis is a fungal infection with a bad prognosis. It usually occurs in immunocompromised patients and manifests itself .Cross-sectional imaging reveals suggestive lesions.